Business advantage : student's book intermediate - Koester, Almut (Cambridge : Cambridge University Press, 2012)
An innovative, new multi-level course for the university and in-company sector. Business Advantage is the course for tomorrow's business leaders. Based on a unique syllabus that combines current business theory, business in practice and business skills - all presented using authentic, expert input - the course contains specific business-related outcomes that make the material highly relevant and engaging.
Keywords: Business education; Business -- Problems, exercises, etc